KEBIJAKAN KEUANGAN NEGARA JERMAN DALAM MENGHADAPI PANDEMI COVID - 19 - Anak Agung Manik Pratiwi (Jurnal Ilmiah Satyagraha, 2021)
Germany is a country in Europe that has successfully faced the impact of the Covid-19 Pandemic on the economy in its country. This study aims to determine the financial policies of the German state in facing the Covid-19 pandemic. This study uses a qualitative descriptive analysis. The results of this study indicate that Germany is implementing the right financial policies to sustain the country's economy due to the Covid-19 Pandemic. The assistance carried out aims to support companies, businesses, entrepreneurs, associations and institutions that are directly and indirectly affected by the temporary closure due to the Covid - 19 pandemic.